2009
DOI: 10.1007/s00439-009-0769-8
|View full text |Cite
|
Sign up to set email alerts
|

The association of the MYH9 gene and kidney outcomes in American Indians: the Strong Heart Family Study

Abstract: Chronic kidney disease (CKD) is an important public health problem in American Indian populations. Recent research has identified associations of polymorphisms in the myosin heavy chain type II isoform A (MYH9) gene with hypertensive CKD in African-Americans. Whether these associations are also present among American Indian individuals is unknown. To evaluate the role of genetic polymorphisms in the MYH9 gene on kidney disease in American Indians, we genotyped 25 SNPs in the MYH9 gene region in 1,119 comparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Recent studies [25,26] based on variants genotyped in Hapmap failed at defining a clear candidate for causal association. If it is in fact true that one single variant can explain the association between this locus and FSGS, then it is likely that it is one of the variants which are highly polymorphic exclusively among Africans, but rare or non-existent in non-Africans, which would explain the lack of replication of association of this locus in other large studies in different populations [27]. The small level of associations observed in Europeans by others [14] could also be explained by low levels of African ancestry in the cases considered or even by the fact that Southern European populations have a 1–3% level of African ancestry due to migrations which took place 50–70 generations ago (private communication with Nick Patterson).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies [25,26] based on variants genotyped in Hapmap failed at defining a clear candidate for causal association. If it is in fact true that one single variant can explain the association between this locus and FSGS, then it is likely that it is one of the variants which are highly polymorphic exclusively among Africans, but rare or non-existent in non-Africans, which would explain the lack of replication of association of this locus in other large studies in different populations [27]. The small level of associations observed in Europeans by others [14] could also be explained by low levels of African ancestry in the cases considered or even by the fact that Southern European populations have a 1–3% level of African ancestry due to migrations which took place 50–70 generations ago (private communication with Nick Patterson).…”
Section: Discussionmentioning
confidence: 99%
“…These genetic associations were evident in African Americans, 90,91 and possibly in Europeans as well, 92 but not in American Indians (Table 1). 93 However, as kidney biopsies were lacking in some of these studies, whether the etiologic label was accurate is difficult to know. In the case of diabetic nephropathy in particular, researchers suggested that the apparent association with the MYH9 locus might actually reflect the presence of nondiabetic kidney disease incorrectly labeled as diabetic nephropathy.…”
Section: The Story Of Myh9 and Apol1 Unfoldsmentioning
confidence: 99%
“…The high frequency of the MYH9 associated haplotypes in African populations led to speculations of selection in Africa ( Figure 2) [42] . The ethnic specificity of the association was explored with different phenotypes and different populations ( Table 2) and subsequent studies provided evidence for a contribution of MYH9 variants in early stages of CKD as well as diabetic and hypertensive-related CKD in both African Americans and Europeans, but not in Native Americans [43][44][45] . However, biopsy-proven forms of CKD were lacking in some of these studies and therefore, as in the case of diabetic and hypertensive nephropathies, researchers suggested that the association with MYH9 could also reflect the presence of non-diabetic and non-hypertensive CKD.…”
Section: Genetic Predisposition To Chronic Kidney Disease In Patientsmentioning
confidence: 99%